Analysis of Doppler Flow Spectra of the Superior Vena Cava in a Canine Model of Acute Thromboembolic Pulmonary Hypertension - Sun, Dan Dan; Chen, Hong Mao; Duan, Yun You; Yuan, Li Jun; Shang, Fu Jun; Liang, Ning Nan; Cao, Wei (Echocardiography (Mount Kisco, N.Y.), 2011)
We aimed to establish a canine model of acute thromboembolic pulmonary hypertension (ATEPH) and to explore the feasibility of diagnosing pulmonary hypertension (PH) through the Doppler flow spectra of the superior vena cava (SVC). A canine model of ATEPH was developed by infusing thrombus into the right femoral vein. The pulmonary arterial pressure was simultaneously measured via a right heart catheter with the guidance of ultrasound. The maximum systolic peak flow velocity (SPV), ventricular reverse peak flow velocity (VRPV), diastolic peak flow velocity (DPV), and atrial reverse peak flow velocity (ARPV) of the SVC were measured by transthoracic echocardiography. ATEPH was successfully established in 24 dogs (88.9%) with the pulmonary arterial systolic pressure (PASP) greater than 30 mmHg. ARPV increased significantly with the increase of PASP, and was positively correlated with PASP (P < 0.001). The ARPV/SPV larger than 0.8 could be better adopted to identify all the subjects with PH in this study. The Doppler flow spectra of the SVC could be employed to assess the severity of ATEPH. (Echocardiography 2011;28:941‐947)